COVID-19 with high-sensitivity CRP associated with worse dynamic clinical parameters and outcomes - Iam-Arunthai, Kunapa; Chamnanchanunt, Supat; Thungthong, Pravinwan; Chinapha, Anongnart; Nakhahes, Chajchawan; Suwanban, Tawatchai; Umemura, Tsukuru (Frontiers in Medicine, 2024)
OBJECTIVE: To evaluate the relationship between high high-sensitivity CRP (hsCRP) in hospitalized COVID-19 patients and their clinical outcomes, including trajectory of hsCRP changes during hospitalization. METHOD AND RESULTS: Patients with positive COVID-19 tests between 2021 and 2023 were admitted in two hospitals. Among 184 adult patients, nearly half (47.3%) had elevated hsCRP levels upon admission, which defined as exceeding the laboratory-specific upper limit of test (>5.0 mg/dL). Clinical outcomes included critical illness, acute kidney injury, thrombotic events, intensive-care-units (ICU) requirement, and death during hospitalization. Elevated hsCRP levels had a higher risk of ICU requirement than those with normal, 39.1% versus 16.5%; adjusted odds ratio (aOR), 2.3 [95% CI, 1.05-5.01]; p= 0.036. Patients with extremely high (>2 times) hsCRP levels had aOR, 2.63 [95% CI, 1.09-6.45]; p <0.001. On the 5th day hospitalization, patients with high hsCRP levels associated with acute kidney injury (aOR, 4.13 [95% CI, 1.30-13.08]; p= 0.016, ICU requirement (aOR, 2.67 [95%CI, 1.02-6.99]; p= 0.004, or death (aOR, 3.26 [95% CI, 1.10-9.65]; p= 0.033. The likelihood of worse clinical outcomes increased as hsCRP levels rose; patients with elevated hsCRP had lower overall survival rate that those with normal (p= 0.02). Subset of high hsCRP patients with high viral load also had shorter half-life compared to those with normal hsCRP level (p= 0.003). CONCLUSION: Elevated hsCRP levels was found to be a significant predictor of ICU requirement, acute kidney injury or death within 5 days after hospitalization in COVID-19 patients. This emphasized the importance of providing more intensive care management to patients with elevated hsCRP.